Model Pengembangan Pencegahan Kesehatan Reproduksi Berbasis Pendekatan Stepwise WHO - Asyima Asyima; Hadriani Irwan (Lembaga Pengembangan Kinerja Dosen, 2024)
The reproductive health problem of couples of childbearing age remains a significant challenge in Indonesian public health, with interventions that tend to be fragmented and less systematic. This study aims to develop and evaluate a comprehensive reproductive health prevention model based on the WHO Stepwise approach for couples of childbearing age in Makassar City, South Sulawesi. The research design used mixed methods sequential exploratory, starting with a qualitative method through focus group discussion and in-depth interviews with 48 participants to explore contextual factors, then continued with a quasi-experimental design on 320 couples in the intervention and control groups. WHO's Stepwise approach includes three phases: assessment, development, and implementation & evaluation. The thematic analysis identified seven major barriers and five supporting factors in reproductive health. The developed model integrates five components: comprehensive education, youth-friendly services, peer education empowerment, family and community engagement, and policy advocacy. Quasi-experimental results showed significant improvements in knowledge (67.3%), positive attitudes (54.8%), and safe reproductive health practices (43.6%) in the intervention group compared to the control (pfeasibility of the WHO Stepwise-based model as a systematic, evidence-based, and multisectoral framework that can be replicated for sustainable reproductive health prevention programs).